Analisis Kesulitan Siswa dalam Mengerjakan Soal pada materi Eksponen - Juju Junengsih; Sutirna Sutirna (Jurnal Ilmiah Dikdaya, 2022)
The fact that there are difficulties in working on the questions on the exponential material is the background of this research. The purpose of this study is to analyze the difficulties of students in working on questions on the Exponential material. This type of research is descriptive research with a qualitative approach. The subjects in this study were 18 students of class X TBSM 2 SMKN 1 Rawamerta. Collecting data in the study from the results of the student's answer test based on the exponential question instrument consisting of two questions. Processing data using the percentage formula to see the level of difficulty. The results of the study showed that there were still many students who had difficulty working on the questions in numbers 1 and 2, this was seen from the number of students who made mistakes in working on the two questions on the exponent material. So it can be concluded that students lack mastery or lack of understanding of Exponential material, especially in its operation of working on Exponential questions.